A prospective study on results of bacterial culture from wound in type III compound fractures - H., Ashwin; Thomas, George (International Journal of Research in Orthopaedics, 2018)
Background: Open fractures still represent a major challenge for the treating surgeon. Sound knowledge of the bacteriological epidemiology and antimicrobial susceptibility helps to prevent complications. Our aim is to study about the common bacteria causing open fracture infection and their antibiotic sensitivity in patients who are admitted in the department of Orthopedics, Government medical college, Kottayam. Methods: A prospective study on 130 patients with type III open long bone fractures were studied for infection during study period of June 2016 to July 2017. After initial debridement and at third day during follow up wound inspection, swabs were taken from wound site. Swabs were send for microscopic examination, culture and antimicrobial susceptibility testing. Results: Out of 130 type III open long bone fractures, 7.7% were having day 0 infection and 25.4% were having day 3 infection. 19.2% of patients developed infection from day 3 onwards. Staphylococcus aureus (37.1%) was the most commonly isolated bacteria from wound. Other organisms isolated were Acinetobacter, Pseudomonas, Klebsiella, E coli, Enterococcus, Streptococcus and Enterobacter. 100% of diabetic patients developed infection on day 3. Gentamicin, amikacin doxycycline, ciprofloxacin, vancomycin, piperacillin + tazobactum and cefoperazone + sulbactum were found to be effective against isolated organisms. Conclusions: Gram positive Staphylococcus aureus was found to be the most common cause of wound infection in type III open fractures. An early adequate wound debridement, proper antibiotic therapy and aseptic post-operative wound care are essential for wound healing and fracture union in an open fracture.